PENGARUH FAKTOR FINANSIAL DAN NON FINANSIAL TERHADAP KETERLAMBATAN PUBLIKASI LAPORAN KEUANGAN : THE INFLUENCE OF FINANCIAL AND NON-FINANCIAL FACTORS ON THE DELAY OF PUBLICATION OF FINANCIAL STATEMENTS - Muthaqin, Maulana; Anisma, Yuneita; Sofyan, Azhari (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2022)
This research intends to investigate the impact of profitability, solvency, liquidity, size of the company, auditor opinion, and audit committee on the overall delay in the release of financial statements. The population of this research is service companies listed on the Indonesia Stock Exchange for the period 2018 to 2020. The sample selection in this research used the purposive sampling technique, from 325 selected populations following the sample criteria to 100 companies. The analytical tool used in this research is logistic regression analysis with IBM SPSS 25 Version. The results of this research found that profitability, solvency, liquidity, company size, auditor opinion, and audit committee had no effect on the total lag in the publication of financial statements.